Weighted Beta CAPM Based On Bank Market Value And Meanings of Financial Data Transparency- Case of 7 Big Listed Commercial Banks In Vietnam - HUY, DINH TRAN NGOC; ANH, VU THI KIM; THACH, NGUYEN NGOC; HAC, LE DINH; ANH, TRAN TUAN; HANH, HOANG THANH (The journal of contemporary issues in business and government, 2021)
Estimating Beta CAPM is a basis for evaluating market risk in the banking sector in Vietnam economy, esp. During pre-low (L) inflation time 2011-2015 and post-L inflation period 2015-2020. The more the economy growing, the more important the role of risk management in commercial bank. Also, the more transparent of financial data, the better the capital flows in the banking and financial market. This research paper aims to figure out in 7 big listed banks in Vietnam including Vietcombank (VCB), Vietinbank (CTG), Asia Commercial Bank (ACB), Sacombank (STB), Navibank (NVB) now become National Citizen Bank, Eximbank (EIB) and Saigon Hanoi Bank (SHB), how much and what is the Weighted Beta CAPM formula based on firm or bank market value during the period 2011-2020 with semiannual data. The result will be a measurement which help us to calculate macro effects on market risk in banking industry. Research findings show us that during post-low inflation time, weighted beta CAPM tends to increase higher, so bank system need to prepare to manage risk better. Last but not least, Our recommendation can be used for reference in many other developing markets. JEL classification numbers: M21, M1, G12, G30